Pengenalan dan Pendampingan Penulisan Karya Tulis Ilmiah pada Siswa MA Tarbiyatus Shibyan Lamongan: Introduction and Assistance in Writing Scientific Writing for MA Tarbiyatus Shibyan Lamongan Students - Malik, Fatus Atho’ul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Writing scientific papers is a valuable skill that students must possess. However, most students continue to face challenges while writing scientific papers, such as a lack of knowledge of concepts and organization, difficulties articulating ideas in writing, and a lack of drive and interest. To address this, students at Madrasah Aliyah Tarbiyatus Shibyan Lamongan participated in community service activities to strengthen their scientific writing skills. This activity, which consisted of three parts (introduction, mentorship, and evaluation), improved students' understanding, skills, and motivation to write scientific papers. Time constraints are an impediment, thus schools should incorporate scientific writing development into the curriculum or extracurricular activities.